Testing the limits of human vision with quantum states of light: past, present, and future experiments - Holmes, Rebecca M; Victora, Michelle M; Wang, Ranxiao Frances; Kwiat, Paul G (SPIE, 2018)
The human eye contains millions of rod photoreceptor cells, and each one is a single-photon detector. Whether people can actually see a single photon|which requires the rod signal to propagate through the rest of the noisy visual system and be perceived in the brain|has been the subject of research for nearly 100 years. Early experiments hinted that people could see just a few photons, but classical light sources are poor tools for answering these questions. Single-photon sources have opened up a new area of vision research, providing the best evidence yet that humans can indeed see single photons, and could even be used to test quantum effects through the visual system. We discuss our program to study the lower limits of human vision with a heralded single-photon source based on spontaneous parametric downconversion, and present two proposed experiments to explore quantum effects through the visual system: testing the perception of superposition states, and using a human observer as a detector in a Bell test.